Exploring the Relationship between Cloud Computing and Blockchain: The Integration of Both Technologies and Its Impact on Ethical Problem Oliver (International Journal of Psychosocial Rehabilitation, 2020)
Cloud computing is a form of technology that has the ability to reduce costs in a business process. However, cloud computing poses an ethical problem, which is the consumers’ right to privacy, and thus it leads to an ethical dilemma that involves the provider, consumer, and government. Another form of technology that recently emerged and has the capability of improving operating activity is blockchain. Blockchain is a form of distributed ledger that has the capability to record transactions in a highly secure manner. There are many studies that investigate the impact of cloud computing as well as blockchain on enterprise-level users. However, there is a limited amount of study that investigates the link between cloud computing and blockchain and its impact on privacy issues. Therefore, this research investigates the relationship between cloud computing and blockchain as well as its impact on privacy issues by exploring the collected secondary data. The research finds that cloud computing could support the implementation of blockchain by nullifying the challenges that blockchain faces in terms of cost, scalability, and performance. This is indicated by the emergence of blockchain as a service (BaaS). The research also finds that blockchain could improve cloud computing security issues in the future. Finally, the research finds that the future integration of both technologies could mitigate the ethical problem of cloud computing, which is the breach of consumers’ privacy.